2020
DOI: 10.1007/s10120-020-01078-0
|View full text |Cite
|
Sign up to set email alerts
|

Glycolytic competence in gastric adenocarcinomas negatively impacts survival outcomes of patients treated with salvage paclitaxel-ramucirumab

Abstract: Introduction For energy production, cancer cells maintain a high rate of glycolysis instead of oxidative phosphorylation converting glucose into lactic acid. This metabolic shift is useful to survive in unfavorable microenvironments. We investigated whether a positive glycolytic profile (PGP) in gastric adenocarcinomas may be associated with unfavorable outcomes under an anticancer systemic therapy, including the anti-angiogenic ramucirumab. Materials and methods Normal mucosa (NM) and primary tumor (PT) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…Then, we tested whether APOC2 can affect the expression of glycolysis‐related proteins (GLUT1, HK2, PKM2, and LDHA). 37 We found that APOC2 knockdown significantly inhibited the expression of HK2 in AGS and BGC‐823 cells, except for GLUT1, PKM2, and LDHA. Regarding whether APOC2 can regulate the expression of lipid metabolism‐related proteins, we verified the relationship between APOC2 knockdown and its closely related lipid metabolism proteins (LIPL, LDLR, and LRP1).…”
Section: Resultsmentioning
confidence: 70%
“…Then, we tested whether APOC2 can affect the expression of glycolysis‐related proteins (GLUT1, HK2, PKM2, and LDHA). 37 We found that APOC2 knockdown significantly inhibited the expression of HK2 in AGS and BGC‐823 cells, except for GLUT1, PKM2, and LDHA. Regarding whether APOC2 can regulate the expression of lipid metabolism‐related proteins, we verified the relationship between APOC2 knockdown and its closely related lipid metabolism proteins (LIPL, LDLR, and LRP1).…”
Section: Resultsmentioning
confidence: 70%
“…Normal cells produce energy through mitochondrial oxidative phosphorylation. The last product of the glycolysis is pyruvate, which enters the mitochondria where it is oxidized by the citric acid cycle to generate energy [ 20 ]. However, in cancer cells, pyruvate is fermented into lactate, even in aerobic conditions and fully functioning mitochondria available.…”
Section: Discussionmentioning
confidence: 99%
“…Lactate is not only a waste for tumors; cancer cells also become more aggressive and resistant to therapy by acidifying their microenvironment. Low pH and lactate enable cancer cells to migrate, invade, promote angiogenesis, immune escape, and radioresistance [ 20 , 21 , 22 ]. The MCT family includes 14 members, among which MCT1-4 are catalyzing the proton-linked transport of pyruvate, lactate, and ketone bodies across the cell membrane [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therapies targeting the Warburg effect have a profound inhibitory effect on tumor progression. In gastric cancer, glycolytic pro ciency negatively affects survival outcomes of metastatic gastric cancer patients treated with paclitaxel-ramucirumab systemic therapy [8]. Notably, several reports have documented the regulators of the Warburg effect in gastric cancer, such as MACC1 [9], FBP1 [10], WTAP [11], and MUC16 [12].…”
Section: Introductionmentioning
confidence: 99%